Evaluation of the Acute and Subacute Toxicity of Aqueous Extract of Coriandrum sativum L. Seeds in Wistar Rats - S'hih, Youssef; Hinad, Ibrahim; Gui, Radia E.; Elhessni, Aboubaker; Mesfioui, Abdelhalim; Loukili, Abdechahid; Ouahidi, Moulay Laarbi (Current Drug Safety, 2023)
Background: In traditional herbal medicine, the Coriandrum sativum (CS) seeds are widely used to prevent and/or treat several diseases. Despite this, research into studying their toxicity is very limited. Objective: This study aims at studying the acute and subacute toxicity of aqueous extract of coriander seeds (AECS) in Wistar rats. Methods: For acute toxicity, five dose levels (500, 1000, 2000, 3000, and 5000 mgkg-1bw) were tested per single oral administration. Subacute toxicity for 28 days was achieved by daily oral administration of AECS at doses of 1000, 2000, and 3000 mgkg-1bw. Results: No deaths or signs were recorded or observed in rats in the five groups and the control group was after 14 days of acute toxicity study. The results of subacute toxicity revealed that the administration of AECS caused a significant difference in the body weight of rats at doses of 2000 and 3000mgkg-1bw, and in the development of movement disturbances, hypoactivity, drowsiness, weakness, and diarrhea, while histopathological examination showed vascular congestion and inflammation of the kidneys as well as hepatic necrosis. The haematological profile showed a significant increase in the number of red and white blood cells, haemoglobin, haematocrit, and a nonsignificant decrease is noticed in neutrophils at a dose of 3000 mgkg-1bw. Conclusion: AECS should be used with caution as it has caused some signs of toxicity and may affect the liver and kidneys if doses are repeated. However, further studies are needed to verify and clarify the toxic aspect of Coriandrum sativum L. seeds.
Keywords: subacute toxicity